If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12x = 72 Solving -12x = 72 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-12'. x = -6 Simplifying x = -6
| 3(5k+7)=(-2)(-4)k | | 4(1-x)+3x=-2(x+1)-(x-3) | | 4x-6=-3x-6 | | 11x=68 | | 4(x+5)+2(x-3)=20 | | 2(3-2x)=7(x+4) | | 4(8+v)=8(3v+9) | | x-2p+10=0 | | 17(x+5)=0 | | -3x+10=2x+8+1 | | 9(y-1)=6(y-3) | | 4(m+9)=-2(m-5)+2 | | 4x+4=32 | | z-(-13)=-8 | | 4x-4-5x=-6+90 | | 3(4-y)=5(y+2) | | m+42=29 | | 8x-3x+19=3x+2 | | -4(2h-7)=5(5-h) | | -5-3+(-2)=n | | 8(n+6)-4=74 | | n-6=21 | | -5-3+(-2)= | | 2x+5-5x=-1 | | y+7=-56 | | x^2+4x-21=0 | | y-7=-56 | | 6x-5(x+3)=10x+10-11x | | .50(6x-4)=4x-9 | | 15x-20=x+6 | | 3-1+5*3= | | 8+5(x-1)=18 |